An Optimization Approach and Environmental Evaluation of Aluminium AA7075 Alloy in Metal Forming Process by Solid State Recycling Hot Press Forging - Ikhwan Shah Tisadi Tukiat; Yusuf, Nur Kamilah; Mohd Amri bin Lajis; Muhamad Haikal Mohd Khaireez (International Journal of Integrated Engineering, 2025)
This study presents the optimization of Direct Recycling Hot Press Forging (DR-HPF) parameters for AA7075 aluminium alloy to enhance mechanical properties and minimize environmental impact. Response Surface Methodology (RSM) with Central Composite Design (CCD) was used to investigate the effects of forging temperature and soaking time on ultimate tensile strength (UTS), elongation to failure (ETF), and global warming potential (GWP). The optimized DR-HPF process, conducted at 480°C and 86 minutes soaking time, achieved a maximum UTS of approximately 251.33 MPa and an ETF of 6.9%, marking significant improvements over conventional recycling methods. Life Cycle Assessment showed a reduction of global warming potential by more than 85% and energy consumption by approximately 69% compared to remelting processes. This work uniquely integrates process optimization and detailed environmental evaluation, advancing sustainable recycling practices for high-performance aluminium alloys.